Clinical Utility of β-Amyloid PET Imaging in People Living With HIV With Cognitive Symptoms. (1st June 2021) - Vera, Jaime H.; Eftychiou, Nicholas; Schuerer, Matti; Rullmann, Michael; Barthel, Henryk; Sabri, Osama; Gisslen, Magnus; Zetterberg, Henrik; Blennow, Kaj; O'Brien, Clara; Banerjee, Sube; Dizdarevic, Sabina
Abstract : Background: Imaging with β-amyloid (Aβ) positron emission tomography (PET) has the potential to aid the diagnosis of the cause of cognitive impairment affecting people living with HIV (PLWH) when neurodegenerative disorders are considered. We evaluated the clinical utility of [ 18 F]Florbetaben (FBB) in PLWH with cognitive symptoms. Methods: Imaging with FBB PET was performed in 20 patients with cognitive concerns about dementia. Neuropsychological testing, plasma neurofilament light protein, plasma Aβ40, Aβ42, and cerebrospinal fluid Aβ42, tau, and HIV RNA were obtained. FBB PET images were assessed visually by 3 readers blinded to the clinical diagnosis and quantitatively by obtaining a composite cortical to cerebellar cortex standardized uptake value ratio (SUVR). FBB SUVR from 10 age-matched healthy controls was compared with SUVR of PLWH. Results: Most participants were men (90%) of white ethnicity (90%) with a median age (interquartile range) of 59 (43–79) years. Median CD4 count was 682 (74–1056). All patients were on combination antiretroviral therapy with plasma and cerebrospinal fluid HIV RNA <40 copies/mL. Fourteen patients had objective cognitive impairment including 2 who met clinical criteria for a diagnosis of dementia. No significant differences in composite SUVRs between PLWH and controls [mean (SD): 1.18 (0.03) vs. 1.16 (0.09); P = 0.37] were observed. Four patients were FBB+ with the highest SUVR in the posterior cingulate, superior temporal, and frontal superior lobe. Amyloid PET results contributed to a change in diagnosis and treatment for 10 patients. Conclusion: [ 18 F]Florbetaben PET has potential as an adjunctive tool in the diagnosis of PLWH with cognitive impairment, increasing diagnostic certainty and optimizing management. Abstract : Supplemental Digital Content is Available in the Text.